Guilty or not guilty by reason of insanity? a comparative study of murderers referred for psychiatric examination by court order - Anat Yaron Antar (BMC, 2023)
Abstract Background Some murders are committed under the influence of a psychotic state resulting from a mental disorder, mainly schizophrenia. According to the law in many countries, people with mental disorders do not have criminal responsibility. They are defined as not guilty due to insanity (insanity defense) and therefore cannot be punished. In Israel, in recent years, more lawyers are requesting psychiatric opinions for the murder defendants they represent. This study aims to explore the differences between two groups of murderers: individuals who committed murder and were found not guilty by reason of insanity (NGRI) and individuals who committed murder and were found responsible and guilty. The comparison is made from a broad perspective by examining sociodemographic factors and psychiatric factors as well as criminological and forensic factors. Methods This study, conducted in Israel, analyzes the sociodemographic and forensic differences between 72 individuals who committed murder and were found not guilty by reason of insanity (NGRI) and 56 individuals who committed murder and were found responsible for their actions and fit to stand trial (guilty). Results The findings show that NGRI participants were more likely to be from central areas, to be Jewish (rather than Arab), to be diagnosed with schizophrenia and have a background of hospitalizations before committing the murder, to have remained at the murder scene and/or called for help, and to be less likely to have committed the murder with a partner. Conclusions The study's findings are explained and the limitations discussed. The findings add to the existing knowledge base about murder by reason of insanity and the differences between NGRI and criminal murderers. The characteristics of the NGRI group found here can help to identify risk groups and to develop and implement prevention programs for people with mental disorders who are at risk of violent behavior.